2003
DOI: 10.4102/sajip.v29i4.126
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress of emergency workers in Gauteng

Abstract: The objectives of this study were to determine the construct validity, internal consistency, construct equivalence and item bias of the Emergency Worker Stress Inventory (EWSI) and to identify occupational stressors for emergency workers. A cross-sectional survey design was used. An accidental sample (N = 405) of emergency workers in Gauteng was used. The EWSI was developed as a measuring instrument and administered together with a biographical questionnaire. Three internally consistent stress factors, namely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Firstly, the results supported a three-dimensional factor structure of the MBI-GS, as has been consistently found across various samples, occupational groups and countries Schutte et al, 2000;Storm, 2002;Taris et al, 1999). The threedimensional factor structure of the UWES was also confirmed, a finding supported by research in different samples, groups and countries (Naudé, 2003;Schaufeli, Martinez et al, 2002;Storm & Rothmann, 2003b). Also, reliability analysis confirmed sufficient internal consistency of the subscales of the MBI-GS and the UWES.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Firstly, the results supported a three-dimensional factor structure of the MBI-GS, as has been consistently found across various samples, occupational groups and countries Schutte et al, 2000;Storm, 2002;Taris et al, 1999). The threedimensional factor structure of the UWES was also confirmed, a finding supported by research in different samples, groups and countries (Naudé, 2003;Schaufeli, Martinez et al, 2002;Storm & Rothmann, 2003b). Also, reliability analysis confirmed sufficient internal consistency of the subscales of the MBI-GS and the UWES.…”
Section: Discussionsupporting
confidence: 67%
“…Despite a few studies of the UWES in South Africa (e.g. Naudé, 2003;Storm & Rothmann, 2003b), more research regarding work engagement in different occupational settings in South Africa is required. Schaufeli, Martinez et al (2002) also found that the hypothesised three-factor model of work engagement was invariant across Spanish, Dutch and Portuguese samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study outcomes on professional caregivers are contradictory, given that some individuals experience high levels of PWB despite a stressful environment (Taubman-Ben-Ari & Weintroub, 2008), while others encounter high levels of chronic stress, burnout and exhaustion due to a stressful environment (Collins, 2008;Naudé & Rothmann, 2003;Rothmann & Malan, 2003). Supporting positive outcome, studies on societies in distress demonstrated a slightly elevated level of wellbeing, regardless of their stressful environments (Keyes, 2007;Ryff, Keyes, & Hughes, 2004).…”
Section: Effects Of Environment and Professional Caregiving Rolementioning
confidence: 96%
“…Attention is increasingly given to professional caregivers based on the intensity of emotional involvement with traumatised people (Bride et al, 2003;Taubman-Ben-Ari & Weintroub, 2008). Researchers disagree about the experience of positive emotional consequences by professional caregivers (Hope, 2006;Naudé & Rothmann, 2003;Rothmann & Malan, 2003).…”
mentioning
confidence: 98%